1993
DOI: 10.1093/infdis/168.2.502
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biotyping and DNA Typing of Candida albicans to the Epidemiology of Recurrent Vulvovaginal Candidiasis

Abstract: One-hundred and five Candida albicans isolates from various anatomic sites of 28 patients, obtained at the onset of two consecutive episodes of well-documented recurrent vulvovaginitis, were typed by methods relying on physiologic or genomic markers. The isolates represented a wide variety of types, and neither a single biotype nor genotype was associated with recurrent vaginitis or a particular body site. Patients generally carried similar strains at various anatomic sites that persisted over time. Genomic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 13 publications
8
37
1
2
Order By: Relevance
“…Vazquez et al (1994) found that eight of ten patients maintained a single strain of C. albicans through sequential infectious episodes but, in two patients, the strain had undergone replacement by another strain. In a similar study, Mercure et al (1993) demonstrated that the majority of patients had maintenance of a single strain, whereas a few patients had strain replacement. These studies were focused only on C. albicans, whereas patients with non-albicans infections were excluded.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Vazquez et al (1994) found that eight of ten patients maintained a single strain of C. albicans through sequential infectious episodes but, in two patients, the strain had undergone replacement by another strain. In a similar study, Mercure et al (1993) demonstrated that the majority of patients had maintenance of a single strain, whereas a few patients had strain replacement. These studies were focused only on C. albicans, whereas patients with non-albicans infections were excluded.…”
Section: Introductionmentioning
confidence: 86%
“…Nonetheless, Lockhart et al (1996) did not find any instances of strain replacement among the sequential isolates of 18 patients studied by using DNA fingerprinting probes. Mercure et al (1993) found that 14 % of recurrent cases were due to colonization by a different strain, by using a Southern hybridization method. By using karyotyping resolved by PFGE, Vazquez et al (1994) found that as many as 20 % of sequential isolates involved strain replacement.…”
Section: Prevalence Of Strain Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, DNA fingerprinting with Ca3 fulfills the general requirements set forth in a previous section of this review for effective fingerprinting methods (288). Ca3 and 27A have been used in a number of epidemiological studies of C. albicans and the highly related species C. dubliniensis (see, e.g., references 6,80,137,164,168,192,196,216,218,227,246,265,FIG. 4.…”
Section: Restriction Fragment Length Polymorphisms With Hybridizationmentioning
confidence: 99%
“…Most longitudinal and/or multiple-site epidemiological work demonstrating strain maintenance in C. albicans has been done with superficial isolates, particularly with cultures from the oral cavities of human immunodeficiency virus (HIV)-infected patients (2,3,6,19,31,48,51,61,71,72,90,96), with vaginal isolates (1,37,49,64,65,73,76,91), with other sources of superficial isolates (4,17,74,97), or with superficial surveillance cultures from hospitalized patients (60,81,89). Some surveys of oral isolates have shown the same strain persisting for months to years (4,17).…”
mentioning
confidence: 99%